2021
DOI: 10.1038/s41598-021-87996-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained high blood pressure and 24-h ambulatory blood pressure monitoring in Tanzanian adolescents

Abstract: Estimates for prevalence of high blood pressure (BP) among adolescents in Africa vary widely and few studies, if any, have documented the results of the recommended stepwise BP screening. In this cross-sectional study in Tanzania, we aimed to estimate prevalence of sustained high BP in 3 public secondary schools using the American Academy of Pediatrics BP screening strategy. On Day 1, one screening automated office BP (AOBP) measurement (Step 1) was followed by two more AOBP measurements (Step 2). Repeat AOBP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Of 79 studies shown in Table 2 , 39 studies (49.4%) used automated BP machines, 33 studies (41.7%) used manual (mercury or aneroid) BP machines, 2 studies (2.6%) used both automated and manual BP machines, and 4 studies (5.1%) used Finapres (Finger artery pressure)—an automated device which records BP measurements “continuously” from a finger artery. Only 3 studies used 24-h ambulatory BP monitoring for confirming HTN ( 4 , 71 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 79 studies shown in Table 2 , 39 studies (49.4%) used automated BP machines, 33 studies (41.7%) used manual (mercury or aneroid) BP machines, 2 studies (2.6%) used both automated and manual BP machines, and 4 studies (5.1%) used Finapres (Finger artery pressure)—an automated device which records BP measurements “continuously” from a finger artery. Only 3 studies used 24-h ambulatory BP monitoring for confirming HTN ( 4 , 71 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…This raises concern about the accuracy of the HTN prevalence estimates and a potential possibility of an overestimated HTN burden ( 3 ). Adolescents are more likely than adults to experience white coat HTN ( 4 , 115 , 116 ). Moreover, majority of adolescents in SSA have never had their BP measured and are therefore more prone to the “white coat effect”, particularly when the BP measurements are taken on one occasion ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that single-day blood pressure measurements have limited accuracy, misclassifying up to 30% diagnosed individuals. 7 , 8 , 9 Therefore, for reliable estimation of blood pressure, most guidelines recommend two or more measurements on separate days. 2 , 10 , 11 , 12 For population surveys, however, revisiting participants on a different day is highly resource-intensive or impossible, especially in remote rural areas or in mobile populations.…”
Section: Introductionmentioning
confidence: 99%